Pengaruh Faktor Internal Dan Eksternal Terhadap Nilai Pembiayaan Murabahah Pada Perbankan Syariah Di Indonesia Periode Januari 2015-Juli 2018
Bank of Sharia is a bank that in its activities, both raising funds and in the context of channeling funds, provides and imposes compensation in accordance with Islamic law. Its activities does not charge interest, or does not pay interest to customers. Rewards received by Islamic banks, as well as those paid by customers depend on the contract and agreement between the customer and the bank. Related to the transaction contract practiced by Islamic banking. The mura>bah